Bowel Ischemia Score Predicts Early Operation in Patients With Adhesive Small Bowel Obstruction. Issue 2 (February 2022) - Morris, Rachel S.; Murphy, Patrick; Boyle, Kelly; Somberg, Louis; Webb, Travis; Milia, David; Tignanelli, Christopher J.; de Moya, Marc; Trevino, Colleen
Background: Nonoperative management of adhesive small bowel obstruction (SBO) is successful in up to 80% of patients. Current recommendations advocate for computed tomography (CT) scan in all patients with SBO to supplement surgical decision-making. The hypothesis of this study was that cumulative findings on CT would predict the need for operative intervention in the setting of SBO. Methods: This is an analysis of a retrospectively and prospectively collected adhesive SBO database over a 6-year period. A Bowel Ischemia Score (BIS) was developed based on the Eastern Association for the Surgery of Trauma guidelines of CT findings suggestive of bowel ischemia. One point was assigned for each of the six variables. Early operation was defined as surgery within 6 hours of CT scan. Results: Of the 275 patients in the database, 249 (90.5%) underwent CT scan. The operative rate was 28.3% with a median time from CT to operation of 21 hours (Interquartile range 5.2-59.2 hours). Most patients (166/217, 76.4%) with a BIS of 0 or 1 were successfully managed nonoperatively, whereas the majority of those with a BIS of 3 required operative intervention (5/6, 83.3%). The discrimination (area under the receiver operating characteristic curve) of BIS for early surgery, any operative intervention, and small bowel resection were 0.83, 0.72, and 0.61, respectively. Conclusion: The cumulative signs of bowel ischemia on CT scan represented by BIS, rather than the presence or absence of any one finding, correlate with the need for early operative intervention.